Influencia de la masa corporal sobre la concentración sérica creatinina en caninos en el barrio Quitus colonial de la ciudad de Quito. - Moya Nuñez, Cynthia Dayana (2021)
Creatinine is a waste molecule generated from muscle metabolism and is synthesized in the body through the liver. The measurement and analysis of creatinine helps us in the process of diagnosing kidney diseases. Therefore, the present project aimed to determine the influence of muscle mass on serum creatinine concentration in domestic canines. For this, an experimental exploratory design study was carried out, which included the collection of blood and urine samples from 30 clinically healthy canines, aged between 14 months to 10 years, they were classified according to muscle mass (1-10kg , 11-25 kg and> 25 kg), sex, race and age (14 months - 6 years and 7 years - 10 years). The study was carried out in the Quitus Colonial neighborhood of Quito city. The blood and urine samples were analyzed in the ANOVA analysis of variance obtaining the following results: the average general index of muscle mass of 18.3 ± 6.78, of creatinine in blood 1.27 ± 0.34 mg / dl and creatinine in urine of 1.36 ± 0.36 mg / dl; being statistically significant with a correlation and positive statistic in blood of r = 0.41 (p <0.05) and in urine the value of r = 0.46 (p <0.05). According to muscle mass, the following results were obtained: Group I blood creatinine (1-10 kg) of 97.24 - 160 μmol / l (1.10 - 1.81 mg / dl), Group II (11-25 kg) of 94.6 - 122.9 μmol / l (1.07 - 1.39 mg / dl) and Group III dogs (> 25 kg) of 90.2 - 138 μmol / l (1.02 - 1.56 mg / l); Urine creatinine in Group I (1-10 kg) of 71.60 - 136.1 μmol / l (0.81 - 1.54 mg / dl), Group II (11 - 25 kg) of 103.43 - 132.60 μmol / l (1.17 - 1.50 mg / dl ) and Group III canines (> 25 kg) of 111.4 - 160 μmol / l (1.26 - 1.81 md / l). According to the age of 14 months-6 years of 1.26 ± 0.33mg / dl in creatinine in blood and 1.29 ± 0.38 of creatinine in urine, in contrast to the age of 7- 10 years the values of 1.32 ± 0.41 mg / dl of creatinine in blood and 1.53 ± 0.21 of creatinine in urine, being statistically significant (p≤0.05). According to the breed: French Poodle of 1.46 ± 0.14 mg / dl of creatinine in blood and 1.49 ± 0.41 of creatinine in urine, whereas the Mestizo breed had 1.21 ± 0.36 of creatinine in blood and 1.31 ± 0.34 of creatinine in urine, being statistically significant (p≤0.05). According to the sex of the canines, in males, the value of 1.33 ± 0.36 mg / dl of creatinine in blood and 1.41 ± 0.33 of creatinine in urine, on the other hand, in females, the value of 1.21 ± 0.33 of creatinine in blood and 1.30 ± 0.39 of creatinine. in urine. The results determined a significant statistical association between the creatinine concentration values obtained for each of the variables.